El Procedimiento Administrativo Sancionador a los Intermediarios de Publicidad que fungen como Pediatras - Fernández Méndez, Colin (2025)
This study seeks to protect newborns’ lives and integrity from a market that prioritizes commercial interests. A key issue is the promotion of breast milk substitutes, where pediatricians’ influence has been distorted by covert advertising, favoring brands over infant health. Regulating their role in formula promotion is essential. To strengthen the analysis, a comparative law approach will be taken, focusing on Uruguay, a country with legal similarities to Peru. This will help assess how the issue has been addressed elsewhere and what measures can be adopted to better protect newborns.